In Silico ADMET and Molecular Interaction Profiles of Phytochemicals from Medicinal Plants in Dakshina Kannada - James, Jainey P.; Ail, Puneeth Deepak; Crasta, Lenisha; Kamath, Rakshith Sudheer; Shura, M. H.; T.J, Sindhu (Journal of Health and Allied Sciences NU, 2023)
The success or failure of a potential drug depends on its absorption, distribution, metabolism, excretion and toxicity (ADMET) characteristics, and these features are usually rate-limiting in the drug development process. Hence, it is essential to know about the predicted ADMET properties of the most promising leads to avoid the risk of late-stage attrition. This project focuses on in silico screening of ADMET properties of phytochemicals found in Dakshina Kannada's medicinal plants, which include Tinospora cordifolia, Azadirachta indica, Ocimum sanctum, and Plectranthus amboinicus, mainly known for their antimicrobial properties.The physicochemical properties, bioactivity scores, ADMET, and molecular interactions of the selected phytoconstituents were determined by QikProp, Molinspiration, ADMETlab 2.0, ProTox-II, and GLIDE. In addition, molecular docking checked for their binding interactions with target proteins 1JIJ and 4 HOE of Staphylococcus aureus and Candida albicans, respectively, as they were well known for their antimicrobial properties. In this studies, rosmarinic acid was well interacted phytochemical with both target proteins and has highest docking score.The physicochemical properties showed that all compounds fell under the recommended molecular weight, volume, and polar surface area range. Xanosporic acid violated two rules of Lipinski's Rule of Five, indicating that it may have problems with oral bioavailability. The ADME properties for most of the phytocompounds were within the recommended ranges; hence, they are promising candidates for drug development. Most phytoconstituents showed good bioactivity scores, indicating they have good druglikeness properties. On the analysis of the toxicity, most of the phytoconstituents were found to be noncarcinogenic and nonmutagenic. Therefore, this data can further be utilized as primary tools for determining the biological actions of these plants.Xanosporic acid was found to violate two out of three rules of Lipinski. Similarly, ursolic acid and oleanolic acid also showed a few undesirable properties. All other compounds otherwise showed desirable properties and hence are promising candidates for drug development. This data can be further utilized as primary tool for determining the biological actions of the plants.
Keywords: physicochemical properties; bioactivity scores; ADMET properties; molecular interactions